Insights into the impact of cross-linking processes on physicochemical characteristics and mucoadhesive potential of gellan gum/retrograded starch microparticles as a platform for colonic drug release - de Oliveira Cardoso, Valéria Maria [UNESP]; Evangelista, Raul Cesar [UNESP]; Daflon Gremião, Maria Palmira [UNESP]; Stringhetti Ferreira Cury, Beatriz [UNESP] (Elsevier, 2020)
Polymer microparticles have been regarded a promising system for drug delivery. In this paper, ionic cross-linking (IC) and dual cross-linking (DC) (ionic/covalent) processes were addressed for the design of innovative microparticles based on gellan gum (GG) and retrograded starch (RS) blends in order to investigate the effect of cross-linking processes on the physicochemical and functional properties of the system. High yield values (>78%) and encapsulation efficiency (around 72%) were achieved. Microparticles were spherical and the particle size ranged from 1016 to 1384 μm. Both cross-linking processes increased the microparticles thermal stability. Starch retrogradation restricted the digestibility by α-amylase pancreatic, so that resistant starch content was above 50%. In general, both IC and DC processes associated to high polymer concentration restricted the microparticles swelling at different pH values (1.2, 7.4 and 6.0) and the increased gellan concentration (2%) improved the mucoadhesiveness. M253ICKT, M255IC-KT and M21053DC-KT microparticles released the lowest amount of drug in acidic media (<17%) and different levels of control of drug release rates were achieved in phosphate buffer, making them potential platforms for colonic drug delivery, attending different therapeutic needs.
Keywords: Controlled release; Dual cross-linking; Ionic cross-linking; Ketoprofen; Mucoadhesion; Polysaccharides